Oxidative stability of goat hamburger added with black sesame extract (Research, Society and Development, 2020)
Goat meat has taken a prominent role for the Northeast region of Brazil, and meat products such as hamburgers are a way of adding value to this raw material. Thus, the objective of this work was to prepare goat hamburgers and evaluate the effect of black sesame extract as a natural antioxidant during 40 days of storage. Four formulations were made: F1 - with bacon and no added antioxidant; F2 - with bacon and addition of 0.5% of black sesame extract; F3 - with soybean oil and without addition of antioxidant and F4 - with soybean oil and addition of 0.5% of black sesame extract. The hamburgers were subjected to centesimal composition analysis and evaluation of oxidative stability for 40 days. The treatments did not differ in terms of moisture and ash contents, with average values of 69.55 and 1.34%, respectively. The lipid content is in accordance with Brazilian legislation (maximum 23%), where it was possible to observe that the addition of black sesame extract, as it is an oilseed, provided an increase in the lipid content between F1 (10.96%) and F2 (11.97%) and between F3 (12.89%) and F4 (15.00%). Regarding the oxidative stability study, the use of saturated fat (bacon) and the action of black sesame as a natural antioxidant provided a lower oxidation of hamburgers, observing values of 11.44; 3.64; 18.07 and 16.04 mg MDA/kg of sample for F1, F2, F3 and F4, respectively. Thus, the black sesame extract was efficient for oxidative control of goat hamburgers.